Le lexique médiéval de la cicatrisation dans les dictionnaires et encyclopédies de médecine des xviiie et xixe siècles. Une enquête dans le Métadictionnaire - Sylvie Bazin-Tacchella (Humanités Numériques)
This article presents the contribution of the Multilingual Medical Metadictionary to the historical study of a medical semantic field in French, that of healing, a key concept in the medieval learned surgeries, which were written in Latin and then translated into the vernacular. Our corpus of terms comes from the 15th-century French translation of Guy de Chauliac’s treatise on wounds in the Chirurgia Magna. Querying the Metadictionary enables us to identify different types of outcome: disappearance or maintenance with or without semantic evolution. When the term searched for is absent from the nomenclature, it may appear in other articles or in lists. We have successively studied the terms cicatrisation, inviscation, conglutination, consolidation, incarnation, and sigillation, and morphologically related terms. Disappearance remains exceptional. Dictionaries often maintain a vocabulary in use, even out of date in the eyes of contemporary science. But an examination of the articles also reveals doctrinal changes and the evolution of descriptive models.